2007
DOI: 10.1002/bdrb.20140
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the potential for developmental toxicity of prenatal exposure to two dietary chromium supplements, chromium picolinate and [Cr3O(O2CCH2CH3)6(H2O)3]+, in mice

Abstract: BACKGROUND: Chromium(III) is generally thought to be an essential trace element that allows for proper glucose metabolism. However, chromium(III) picolinate, Cr(pic) 3 , a popular dietary supplement form of chromium, has been shown to be capable of generating hydroxyl radicals and oxidative DNA damage in rats. The cation1 , Cr3, has been studied as an alternative supplemental source of chromium. It has been shown to increase insulin sensitivity and lower glycated hemoglobin levels in rats, making it attractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 41 publications
(52 reference statements)
3
22
1
2
Order By: Relevance
“…Recently, our laboratory published findings that prenatal exposure to high levels of chromium picolinate resulted in an increased incidence of cervical arch defects [28]. However, although our more recent findings were similar in direction, the differences from control values for this parameter were not statistically significant [29].…”
Section: Introductionsupporting
confidence: 40%
“…Recently, our laboratory published findings that prenatal exposure to high levels of chromium picolinate resulted in an increased incidence of cervical arch defects [28]. However, although our more recent findings were similar in direction, the differences from control values for this parameter were not statistically significant [29].…”
Section: Introductionsupporting
confidence: 40%
“…However, the current work utilizing male mice, in combination with earlier studies by Bailey, et al [14][15][16], indicates that in mammals, independent of whether [Cr(pic) 3 ] is …”
Section: Discussionsupporting
confidence: 51%
“…Our laboratory has published findings that mated female mice exposed to high levels of chromium picolinate resulted in progeny with an increased incidence of cervical arch defects [14]. However, although a similar trend was observed in more recent studies, the differences from control values for this parameter were not statistically significant [15,16].…”
Section: Introductionsupporting
confidence: 65%
“…Interestingly, several developmental studies on another chromium supplement, namely chromium picolinate (CrPic) showed inconsistently results. Although CrPic was found to be non-teratogenic, exposure of pregnant mice to CrPic resulted in skeletal defects in their offsprings [26][27][28].…”
Section: Discussionmentioning
confidence: 99%